Chile's "Neoliberal" Retirement System? Concentration, Competition, and Economic Predation in "Private" Pensions. Issue 2 (June 2015) - Hyde, Mark; Borzutzky, Silvia
<x xml:space="preserve">Abstract</x> In 1981, Chile's military dictatorship introduced a major reform of the retirement system, replacing a set of long‐standing public pension arrangements with a system of privately administered, defined contribution, individual accounts. For a wide spectrum of scholarly opinion, the provisions that were created by this reform represented the institutional embodiment of neoliberalism, emphasizing individualism, competition, and economic efficiency. We reject this characterization of the Chilean pension reform. In particular, this article evaluates Chile's private retirement system against pension design principles that would be suggested by neoliberalism, focusing on concentration in the pension fund management industry. We argue that Chile's experiment in pensions' "privatization" was deeply conservative, creating a state‐organized system of market privilege rent‐seeking that was biased in favor of big business. But neither neoliberalism nor conservatism are satisfactory approaches to retirement income protection, and Chileans would be best served by a well‐designed social insurance pillar.